Two-stage-sparse algorithm for carrier Doppler-shift acquisition in space communications - ZHANG Zhaowei; LIU Lin; LIU Hui; WU Tong; ZHU Minglei; PAN Su (物联网学报)
In space communications, the signal faces long-distance transmission and a high-dynamic relative movement. The long-distance transmission results in a very low signal-to-noise ratio (SNR) and the high-dynamic relative movement causes a high-dynamic Doppler-shift on the carrier. To address the low SNR, the traditional acquisition method requires the long-time accumulation of many received signals. However, during the long-time accumulation, the high-dynamic Doppler-shift causes the serious energy dispersion problem. To solve the problem, a two-stage-sparse (TSS) algorithm was proposed to acquire the Doppler-shift. The proposed TSS algorithm firstly used the coarse acquisitions to construct a coarse sparse-search-range, then selected some large elements to construct a fine sparse-search-range, and finally searched the largest element as the acquisition result. Because the sparse-search-range only covers a narrow frequency range, the TSS algorithm excludes more noise elements, thus allowing the signal element to become the largest element. The theoretical analysis and simulation results show that the proposed TSS algorithm significantly increases the acquisition probability.